2019
DOI: 10.1177/1350650119858243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angular misalignment on the dynamic characteristics of externally pressurized air journal bearing

Abstract: This paper studies the effect of angular misalignment on the dynamic characteristics of externally pressurized air journal bearing with four degrees of freedom. The linear perturbation method is applied to the Reynolds equation to obtain the steady-state equation and perturbation equations, and then the finite difference method and an iterative method are used to solve the Reynolds equation. Various eccentricity ratios and rotating speeds are taken into considerations for the comparisons of dynamic stiffness c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…This phenomenon is mainly due to the change in pressure difference, which can increase the pressure of the whole gas gap region, making the value of gas pressure rapidly greater. When the pressure of the sealing medium is low, the gas expansion between the rotating pairs is weak (Shi et al 2019(Shi et al , 2020, which gives rise to a decrease in the gas temperature. As the inlet pressure increases, the flow rate of the medium gas and the velocity gradient also increases.…”
Section: Theoretical Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is mainly due to the change in pressure difference, which can increase the pressure of the whole gas gap region, making the value of gas pressure rapidly greater. When the pressure of the sealing medium is low, the gas expansion between the rotating pairs is weak (Shi et al 2019(Shi et al , 2020, which gives rise to a decrease in the gas temperature. As the inlet pressure increases, the flow rate of the medium gas and the velocity gradient also increases.…”
Section: Theoretical Calculationmentioning
confidence: 99%
“…The floating ring seal is an advanced non-contact seal. Its working principle is chiefly originated from gas lubricated bearing (Hou et al 2020;Shi et al 2020), and offers the advantages of no wear, low leakage, and compact structure. Therefore, it is widely applied to shaft seals of compressors, gas turbines, engines, and other equipment (Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ảnh hưởng của khối lượng mất cân bằng đến dao động của trục chính được nghiên cứu dựa trên mô hình đề xuất [2][3][4]. Trong nghiên cứu nghiên cứu ảnh hưởng của sai lệch góc đối với các đặc tính động học của ổ khí tĩnh chịu áp suất bên ngoài với bốn bậc tự do nhóm nghiên cứu Jianghai Shi và một số tác giả đã so sánh các hệ số độ cứng động và hệ số giảm chấn của ổ trục không khí dưới các góc nghiêng khác nhau [5][6][7]. Các nghiên cứu về hiệu suất ổ khí tĩnh cũng đã được nghiên cứu với những ảnh hưởng khác nhau đã được đưa ra để cải thiện độ cứng vững khi làm việc [8,9].…”
Section: Giới Thiệuunclassified
“…Li and Liu 11 studied spindle rotation accuracy under different cutting loads, imbalance response, and stability, and concluded that the tilt of the spindle rotor has a distinct impact on the above indices. Shi et al 12 researched the characteristics of the five degrees of freedom aerostatic spindles of fly cutting machine tools and showed that pressure distribution, stiffness, and the damping coefficients of the spindle exhibited significant variations due to changes in spindle rotation speed and tilt angle. Dal and Karaçay 13 studied the relationships between air film thickness, pressure distribution, and bearing capacity of the spindle under the combined action of different inclination angles, rotating speed, and eccentricity.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et. al researched the characteristics of the five degree-of-freedom aerostatic spindles of fly-cutting machine tools, and the conclusion showed the pressure distribution, stiffness, and damping coefficients of the spindle had significant variation due to the changes of the spindle rotation speed and tilt angle [13] . Abdurrahim studied the variation rules of air film thickness, pressure distribution, and bearing capacity of the spindle under the combined action of different inclination angles, rotating speed, and eccentricity [14] .…”
Section: Introductionmentioning
confidence: 99%